2013
DOI: 10.1111/jfd.12027
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus epizootic in cultured Pacific white shrimp Litopenaeus vannamei (Boone) in Taiwan

Abstract: White spot syndrome virus (WSSV) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp Litopenaeus vannamei (Boone) were collected from 220 farms in Taiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction (PCR) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…), which has a high virulence and causes great economic losses when it infects Litopenaeus vannamei (Boone) and Penaeus monodon (Fabricius; Cheng et al . ; Dutta et al . ), the two species that currently support the global shrimp aquaculture industry (Walker & Winton ).…”
Section: Introductionmentioning
confidence: 99%
“…), which has a high virulence and causes great economic losses when it infects Litopenaeus vannamei (Boone) and Penaeus monodon (Fabricius; Cheng et al . ; Dutta et al . ), the two species that currently support the global shrimp aquaculture industry (Walker & Winton ).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of WSSV in cultured P. vannamei is reported from Iran (Pazir et al, 2011), Taiwan (Cheng et al, 2013), Equador (Rodriguez et al, 2003) and Indonesia (Ferasyi et al, 2015). WSSV infection has caused mass mortalities of farmed P. vannamei, bringing huge loss to shrimp farmers around the world like Ecuador (Calderon et al, 1999), Brazil (Cavalli et al, 2008) and Iran (Afsharnasab et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…When infected under culture conditions, WSSV prevalence in L. vannamei ranged from 40 to 71% 124 and was 100% during a WSD outbreak. 124 In contrast, several authors showed that the prevalence of WSSV infection in P. monodon broodstock collected at sea, varied between seasons. [125][126][127] In the Philippines, WSSV prevalence was higher during the dry season (10%) than during the wet season (0.3%), 126 while it was the opposite in Thailand 125 and India.…”
Section: The Reservoir Hostmentioning
confidence: 99%